Analisa Faktor Penyebab Kejadian BBLR di Wilayah Kerja Dinas Kesehatan Kota Solok - Dewi Rahmadani; Resty Noflidaputri; Visti Delvina (Publikasi Indonesia, 2022)
Riskesdas 2020 data obtained from West Sumatra with birth weight <2500 grams as much as 4.6%. Solok City Health Office in 2020 the number of births with LBW as many as 65 people until December, with the number of births 1331 people the percentage is 4.8%. The purpose of this study was to determine the Analysis of Factors Causing the Incidence of LBW. This research is qualitative with a phenomenological approach, the instrument in this study is an interview guide, a voice recorder. In this study, 23 informants were found consisting of 1 Head of the Solok City Health Office, 4 Heads of Public Health Centers, 4 midwives in charge of MCH, 4 regional supervisory midwives, 4 nutritionists, 6 mothers who had babies with LBW. This research was conducted at the Public Health Center of the Solok City Health Office. The results of the input research obtained that policies, funds, human resources, facilities and infrastructure, were in accordance with the procedures and policies of the Solok City Health Office. The process of getting planning, organizing, monitoring, evaluating, has been going well, it's just that there are still problems in recording and reporting, the blank is not filled in. The output obtained is that the scope of activities has reached the target, but the quality of service is still lacking because there are still many officers who already have competence but have not been able to apply it to the community. The conclusion is that the scope of activities has reached the target but the quality of service is still lacking because there are still many officers who already have competence but have not been able to apply it to the community. It is recommended that officers who are in the work area of the Solok City Health Service, especially midwives, can work well, if there are cases they are handled properly and for recording there are officers, especially LBW, to get immediate treatment by providing training.